Local hunting practices and perceptions regarding the distribution and ecological role of the Large Flying Fox (Chiroptera: Pteropodidae: Pteropus vampyrus) in western Sarawak, Malaysian Borneo - Mohd Azlan, Jayasilan; Joon, Yee Yong; Nabila Norshuhadah, Mohd Hazzrol; Philovenny, Pengiran; Arianti, Atong; Sheema, Abdul Aziz (Wildlife Information Liaison Development Society, 2022)
Pteropodids such as flying foxes are declining rapidly across their range due to human activities, despite their benefit to humans through ecosystem services. The Large Flying Fox Pteropus vampyrus had a wide distribution across Borneo, but is now severely reduced in numbers, and rarely sighted. In order to develop effective conservation and management prescriptions for this species, updated information on its distribution, movement patterns, and the impact of anthropogenic pressure on its survival is crucial. As such, a questionnaire survey was conducted in western Sarawak to determine the occurrence of this species, and the conservation awareness for the species amongst local communities. The survey was conducted at nine sites during November 2018 – March 2019, involving a total of 123 respondents, including hunters (20%) and consumers (35%) of P. vampyrus. Respondents reported that P. vampyrus appears sporadically around the western tip of Borneo, and around the interior parts of western Sarawak, with more than half (51%) of the reported sightings in the interior occurring at fruit orchards during the fruiting and flowering seasons. Despite hunting and consuming this species, over 60% of the respondents felt that P. vampyrus could become an eco-tourism product in their area. Although many respondents viewed flying foxes as pests (47%) or food (52%), there was remarkably high awareness of the ecological roles and conservation needs of this species (76%), suggesting potentially strong support for flying fox conservation at the local level.Challenges associated with the enforcement of wildlife law in the remote parts of Sarawak need to be addressed, alongside strategic education and awareness efforts, which are all vital to achieve successful conservation and protection of this ecologically important species.